Contributions of Demographics, Language Learning Experience, and Cognitive Control to Chinese Reading Comprehension - Xie, Zhilong; Wang, Wei; Chu, Xiaying; Qiu, Qing; Yuan, Fangfang; Huang, Jinwen; Chen, Meijing (Frontiers in Psychology, 2021)
The study investigates whether learners’ demographics (e.g., age, education, and intelligence-IQ), language learning experience, and cognitive control predict Chinese (L2) reading comprehension in young adults. Thirty-four international students who studied mandarin Chinese in mainland China (10 females, 24 males) from Bangladesh, Burundi, Congo, Madagascar, Nigeria, Rwanda, South Africa, and Zimbabwe were tested on a series of measures including demographic questionnaires, IQ test, two cognitive control tasks (flanker task-measuring inhibition and Wisconsin Card Sorting Test-WCST measuring mental set shifting), and a Chinese reading comprehension test (HSK level 4). The results of correlation analyses showed that education, L2 learning history, L2 proficiency, and previous category errors of the WCST were significantly correlated with Chinese reading comprehension. Further multiple regression analyses indicated that Chinese learning history, IQ, and previous category errors of the WCST significantly predicted Chinese reading comprehension. These findings reveal that aside from IQ and the time spent on L2 learning, the component mental set shifting of cognitive control also predicts reading outcomes, which suggests that cognitive control has a place in reading comprehension models over and above traditional predictors of language learning experience.